Effects of spray-dried animal plasma on growth performance, survival, feed utilization, immune responses, and resistance to Vibrio parahaemolyticus infection of Pacific white shrimp (Litopenaeus vannamei) - Chuchird, Niti; Rairat, Tirawat; Keetanon, Arunothai; Phansawat, Putsucha; Chou, Chi-Chung; Campbell, Joy (PloS one, 2021)
Spray-dried animal plasma (SDP) in feed for several animal species provides health benefits, but research about use of SDP in shrimp feed is very limited. The objectives of the present study were to investigate the effects of dietary SDP on growth performance, feed utilization, immune responses, and prevention of Vibrio parahaemolyticus infection in Pacific white shrimp ( Litopenaeus vannamei ). In Experiment 1, the post-larvae were divided into five groups (four tank/group and 80 shrimp/tank) and fed four times daily diets with porcine SDP at 0, 1.5, 3, 4.5, and 6% of the diet for 45 days. In Experiment 2, the surviving shrimp from Experiment 1 were redistributed into six groups: four SDP groups as in Experiment 1 plus the positive and negative controls (four tank/group and 30 shrimp/tank). They were then challenged with V . parahaemolyticus by immersion at 10 5 colony-forming units (CFU)/mL and were fed with the same diets for another 4 days. In Experiment 1, shrimp fed 4.5% or 6% SDP diets had significantly higher body weight, survival rate, and improved feed conversion ratio. The immune parameters (total hemocyte count and phagocytic, phenoloxidase, and superoxide dismutase activities) of the shrimp fed 3–6% SDP diets also showed significant enhancement compared to the control. In Experiment 2, the survival rates of the 3–6% SDP groups were significantly higher than the positive control at day 4 after the immersion challenge. Likewise, the histopathological study revealed milder signs of bacterial infection in the hepatopancreas of the 3–6% SDP groups compared to the challenged positive control and 1.5% SDP groups. In conclusion, shrimp fed diets with SDP, especially at 4.5–6% of the diet, showed significant improvement in overall health conditions and better resistance to V . parahaemolyticus infection.